Metabolomic Insights into Sheep Milk: Advancing the Development of Healthier Functional Foods. - GILL, AAKASH; BOHRA, MEGHA; ADIL, SHAIKH; BIHOLA, ANKIT; VASHISHT, PRANAV; DWIVEDI, ABHISHEK; VERMA, DIGVIJAY (Current Research in Nutrition & Food Science, 2026)
Sheep milk, a crucial health-promoting dairy product, holds nutraceutical significance in functional nutrition, as demonstrated by metabolomics studies. Compared to staples like cow and goat milk, sheep milk has a significantly higher concentration of various proteins, fats, vitamins, and bioactive components such as omega fatty acids, conjugated linoleic acid (CLA), and peptides with antioxidative and anti-inflammatory properties. Metabolomics, an advanced analytical tool that captures the multivariate profiles of biological samples, is essential for understanding the bioactive characteristics of sheep milk. The metabolite profile of fresh sheep milk varies significantly based on breed, stage of lactation, diet fed to the animals, and environmental factors, presenting promising opportunities for functional food development and genetic identification tailored to individual nutrition. Both specific and non-specific metabolomics approaches, including Nuclear Magnetic Resonance (NMR), Mass Spectrometry (MS), Liquid Chromatography – MS (LC-MS), and Gas Chromatography-MS (GC-MS), facilitate hypothesis-driven and hypothesis-generating studies, aiding in the understanding of the nutritional values and presence of novel bioactive compounds in sheep and goat milk. Future directions for metabolomics research may focus on enhancing existing metabolomics techniques, developing a more extensive database of metabolomic data, and correlating metabolomics outcomes with other omics data. Improvements in high-resolution MS and bioinformatics could unveil more information about sheep milk for the dairy industry, particularly regarding the functional properties of milk to meet distinct health needs. This review advocates for greater standardization in sheep milk research to effectively harness its nutritional and therapeutic potential in consumer healthcare products.